Treatment with 7% and 10% CO2 enhanced expression of IL-1β, TNF-α, and IL-6 in hypoxic cultures of human whole blood. Issue 4 (April 2020) - Ding, Hongguang; Li, Ya; Li, Xusheng; Liu, Xinqiang; Chen, Shenglong; Liu, Mengting; Zeng, Hongke
Objective: This study investigated whether hypercapnia influenced the inflammatory response of hypoxic blood. Methods: Human whole blood was cultured with 0.2% oxygen (O2 ) and treated with 5%, 7%, or 10% carbon dioxide (CO2 ). Interleukin (IL)-1β, tumor necrosis factor (TNF)-α, and IL-6 were evaluated in whole blood cultures. Reactive oxygen species (ROS) production and expression levels of caspase-1 and IL-1β were evaluated in THP-1 monocytic cells. Results: IL-1β, TNF-α, and IL-6 levels were higher in the hypoxia + 7% CO2 group than in the hypoxia + 5% CO2 group. The hypoxia + 10% CO2 group had the highest IL-1β, TNF-α, and IL-6 levels, compared with the hypoxia + 7% CO2 and hypoxia + 5% CO2 groups. Expression levels of IL-1β, TNF-α, and IL-6 were significantly negatively correlated with pH levels in the cell culture medium. Treatment with 7% and 10% CO2 increased the production of ROS and the expression of caspase-1 and IL-1β in hypoxia-activated THP-1 cells. Conclusions: High levels of CO2 treatment increased expression levels of IL-1β, TNF-α, and IL-6 in hypoxic whole blood cultures. High levels of CO2 -induced ROS overproduction and NLRP3 inflammasome activation in monocytes may comprise a target to mitigate the inflammatory response of hypoxic blood.